Doença vestibular periférica decorrente de osteoartropatia temporoioídea em um eqüino - Borges, Alexandre Secorun [UNESP]; Nicoletti, José Luiz de Mello [UNESP]; Thomassian, Armen [UNESP]; Bandarra, Ênio Pedone [UNESP]; Angeli, Ana Laura [UNESP] (Universidade Federal de Santa Maria (UFSM), 2003)
Um eqüino com 22 anos de idade apresentou síndrome vestibular periférica associada à paralisia de nervo facial esquerdo devido à osteoartropatia temporoioídea. O exame endoscópico das bolsas guturais mostrou alteração de contorno da bula timpânica esquerda e aumento de volume da extremidade proximal do osso estiloióide do mesmo lado.

A 22-year-old gelding showed vestibular syndrome associated with left facial nerve paralysis due to temporohyoid osteoarthropathy and the diagnostic was confirmed by guttural pouch endoscopic examination. The exam revealed abnormal contour of the left tympanic bulla and an enlargement of the proximal part of the left stylohyoid bone.
Peripheral vestibular disease associated with temporohyoid osteoarthropathy in a horse
Keywords: sistema vestibular; nervo facial; endoscopia; bolsa gutural; vestibular system; facial nerve; endoscopic examination; guttural pouch